Community readiness assessment for a community-based collecting and archiving project for contemporary komiks - Boquiren, Alain Andrew S.; Cabbab, Johann Frederick A.; Olgado, Benedict S. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2018)
Philippine comic books (komiks) have never been taken seriously enough to be properly archived and preserved like other forms of literature. It was the local comic book community who have started an independent practice of promoting, distributing, and preserving komiks during the 2000s, the same decade that local comic book circulation died down. A select few of these nonprofessional practices have started to veer towards community archiving, an archival phenomenon recently recognized by the profession. As of this writing, these would-be community archiving efforts are limited in scope and have yet to develop to involve a larger part of the community.
This study assesses how willing and ready the local komiks community in the National Capital Region is to collaborate in a community-based archiving initiative. A project plan based on the findings is also developed to help bridge the gap between the grassroots komiks community and archive practitioners, which can be used as a starting point for a komiks preservation practice amongst community members.
Thesis (Master of Library and Information Science)--University of the Philippines Diliman